PENGARUH CURING TIME DAN PENGARUH AIR PADA LAPISANBER-TACK COAT TERHADAP KINERJA TAHANAN GESER PADA INTERFACE LAPISAN BERASPAL - Ida Rumkita; R. Anwar Yamin (Direktorat Bina Teknik Jalan dan Jembatan, 2006)
In a multi layers pavement structure, each layer should be integrated. In overlay work tack coat is used to bond between existing and new layers.New asphalt mixture is placed after the application of tack coat in order to allow the oil in tack coat to evaporate.The purpose of the research is to find out the influence of curing time and water in coated layers on the shear strength of asphalt layer in terface. A specimen was made using MC- 250 as tack coat, curing time duration and water influence were variously set up.The shear strength on specimen interface was tested by direct shear using normal loading of 20 kg. Research result indicates that curing time duration of tack coat significantly influences the shear strength. If the application is done in the range of setting time of tack coat, the shear strength generated by tack coat in asphalt layer interface nearly reached the maximum value and the shear occurred among layers is small. For liquid asphalt MC-250,setting time occurred at the range of 45 – 120 minutes.Therefore,to reach optimum result the application should be performed at that range.The research result also shown that water gives negative influence on shear strength generated by tack coat. For 2; 1 and 0,5 hour tack coat cure, they were allowed dump by water for 2; 1,5 and 0,5 hours respectively.